2011
DOI: 10.1111/j.1747-0285.2011.01160.x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of New Antifungal Leads via Pharmacophore Modeling and QSAR Analysis of Fungal N‐Myristoyl Transferase Inhibitors Followed by In Silico Screening

Abstract: N-Myristoyl transferase is an essential enzyme for fungal growth and survival. The continuous interest in the development of new antifungal agents prompted recent interest in developing new potent inhibitors of fungal N-myristoyl transferase. In this context, we combined pharmacophore and QSAR modeling to explore the structural requirements for potent N-myristoyl transferase inhibitors employing 55 known N-myristoyl transferase ligands. Four binding pharmacophore models emerged in the optimal QSAR equations (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…Compound 33, found by Taha et al, [42] was found to be a moderately potent NMT inhibitor, with an MIC value of 289 mg mL À1 on the basis of the pharmacophore modeling, QSAR analysis, and screening of NMT in silico. These methods proved to be useful tools in the search for potential antifungal agents based on NMT inhibition.…”
Section: Othersmentioning
confidence: 95%
See 3 more Smart Citations
“…Compound 33, found by Taha et al, [42] was found to be a moderately potent NMT inhibitor, with an MIC value of 289 mg mL À1 on the basis of the pharmacophore modeling, QSAR analysis, and screening of NMT in silico. These methods proved to be useful tools in the search for potential antifungal agents based on NMT inhibition.…”
Section: Othersmentioning
confidence: 95%
“…Therefore, further modifications are necessary to obtain new compounds with potent activity against both A. fumigatus and C. albicans NMTs, thereby inhibiting the growth of both A. fumigatus and C. albicans. [42,50] The mechanistic study showed that the imidazole nitrogen atom is approachable for hydrogen bond interaction with active site residues, and its biological activity is closely linked to the conformational rigidity of the substituent at the C4 position of the benzofuran ring, as determined by three-dimensional quantitative structure-activity relationship (3D-QSAR) analysis.…”
Section: Benzofuransmentioning
confidence: 99%
See 2 more Smart Citations
“…The pharmacophore models (Hypo4/10 and Hypo32/8) were used as 3D search queries to mine 3D libraries for new DPP IV inhibitors, while the QSAR model predicted their biological activities and therefore prioritize them for in vitro evaluation [17, 18]. The use of this inventive approach was previously reported in the discovery of new inhibitory leads against cholesteryl ester transfer protein [23-25], β-D-glucosidase [26], β-D-galactosidase [27] and N -myristoyl transferase [28]. …”
Section: Introductionmentioning
confidence: 99%